TRANSFORMATIONAL LEADERSHIP ON JOB SATISFACTION AMONG REGISTERED NURSES CARING PERSPECTIVE: A SYSTEMATIC REVIEW - Elizabeth Vallejo; Carlo Bryan Borrico (Nurse and Health)
Background: The healthcare profession face scarcity due to increased global demand for registered nurses. The inadequacy of the healthcare workforce is a critical concern in an organization, as it is difficult to retain and recruit qualified staff to deliver safe and quality outcomes in the provision of care. Numerous studies identify transformational leadership style as an effective style to foster job satisfaction among licensed nurses.